2017
DOI: 10.1021/acsmacrolett.7b00111
|View full text |Cite
|
Sign up to set email alerts
|

Triclocarban: Commercial Antibacterial and Highly Effective H-Bond Donating Catalyst for Ring-Opening Polymerization

Abstract: The antibacterial compound, triclocarban (TCC), is shown to be a highly effective H-bond donating catalyst for ring-opening polymerization (ROP) when applied with an H-bond accepting base cocatalyst. These ROPs exhibit the characteristics of “living” polymerizations. TCC is shown to possess the high activity characteristic of urea (vs thiourea) H-bond donors. The urea class of H-bond donors is shown to remain highly active in H-bonding solvents, a trait that is not displayed by the corresponding thiourea H-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 34 publications
5
55
0
Order By: Relevance
“…Compared to the bifunctional catalysts, the advantage of hydrogen bond donor (HBD) in cooperation with a hydrogen bond acceptor (HBA) is a straightforward synthetic access from the commercial compounds. Kiesewetter and coworkers reported that the HBDs—urea and thiourea stand out among the controlled ROP of lactones, because of their precise controls for polymerization over transesterification . The urea HBD has better activity and controllability than the thiourea in the ROP of lactones (lactide excluded).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the bifunctional catalysts, the advantage of hydrogen bond donor (HBD) in cooperation with a hydrogen bond acceptor (HBA) is a straightforward synthetic access from the commercial compounds. Kiesewetter and coworkers reported that the HBDs—urea and thiourea stand out among the controlled ROP of lactones, because of their precise controls for polymerization over transesterification . The urea HBD has better activity and controllability than the thiourea in the ROP of lactones (lactide excluded).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis and characterization of polyesters Polyesters (PCL, PLA, and PGA) were synthesized with low Đ and with targeted molecular weights via ring-opening polymerization. 38 Molecular weights and dispersities were analyzed by GPC, NMR, and XPS and were found to be comparable (Table 1). PCL and PLA molecular weights were most reliably determined by THF GPC; however, the molecular weight of PGA was determined most accurately by 1 H-NMR end-group analysis due to limited solubility in most solvents.…”
Section: Resultsmentioning
confidence: 95%
“…An organic coordination catalyst system was selected in order to avoid tin toxicity, while providing characteristics consistent with living polymerizations. 38 To verify that the polymerization was controlled, PCL was observed by 1 H-NMR to give a linear conversion to molecular weight (ESI Fig. S1 †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with a base, the binary catalytic systems exhibited an excellent performance in both activity and selectivity in the preparation of linear polymers. [ 41–46 ] However, it was still a challenge to prepare polyesters with high molecular weight based on the (thio)urea catalysts. To our knowledge, there were only few reports about the synthesis of polyesters with a molecular weight higher than 100 kg mol −1 with the (thio)urea systems.…”
Section: Introductionmentioning
confidence: 99%